خصائص اللُّغة الشِّعرية في ديوان :«الأغاريد»لسيف محمد المري (مجلة إحالات, 2025)
ملخص: يعد الشاعر الإماراتي سيف المري أحد أبرز الشعراء الذي عرفتهم دولة الإمارات العربية المتحدة في العصر الحديث، فهو صوت شعري متميز،إنه واحد من رواد الاتجاه الوجداني الرومانسي،وأحد أبرز شعراء الغنائية الوجدانية الجديدة في الخليج العربي،ويعد من أشرق الوجوه الشعرية التي أسهمت في إثراء الحركة الأدبية، والإعلامية بدولة الإمارات العربية المتحدة،فهو يجمع بين الإبداع الشعري، والقصصي،والكتابة الصحفية. وتهدف هذه الدراسة الموسومة ب: «خصائص اللغة الشعرية في ديوان(الأغاريد)لسيف محمد المري »،إلى تقديم دراسة تحليلية في مجموعة من أشعاره المتميزة، من خلال ديوانه الشعري الأول الذي صدر سنة:2001م، تحت عنوان:«الأغاريد». وقد توقفت في هذه الدراسة مع عدة قضايا دقيقة تتصل بالكون الشعري عند سيف المري،والذي يتسم بالرحابة، والاتساع،و يتمحور بين تصوير العاطفة، والوجدان،وتصوير الحب، والجمال، وأغلب قصائده تتوزع بين الرومانسية الذاتية، والرومانسية الإنسانية،وقدمت مجموعة كبيرة من النتائج التي تتصل بالخصائص الفنية لشعر سيف المري من خلال ديوان(الأغاريد) . وقد قامت الدراسة على تقسيم الموضوع إلى ما يأتي : -مقدمة أولاً :خصائص اللغة الشعرية عند سيف المري من خلال ديوان(الأغاريد). ثانAbstract: Emirati poet Saif al-Marri is one of the most prominent poets of the modern era in the UAE. He is a distinguished poet. He is one of the pioneers of the romantic emotional trend. He is one of the most famous poets of the new song in the Arabian Gulf and one of the brightest poets who contributed to enriching The literary and media movement in the United Arab Emirates combines poetic creativity, fiction and journalism. This study, which is based on the characteristics of the poetic discourse at Saif al-Marri, aims to present an analytical study to a group of distinguished poems through its first poetry library, which was published in 2001 under the title "Al-Agharid" and its second book, »And issued in 2004. In this study, I have stopped with a number of delicate issues related to the mystical universe of Saif al-Marri, which is characterized by spaciousness. It concentrates between the depiction of emotion, conscience, the depiction of love and beauty, and most of his poems are divided between self-romance and human romance. Which relate to the technical characteristics of Saif al-Marri's hair. The study divided the subject into the following: -an introduction First: Introduction to the world of poet Saif al-Marri. Second: Characteristics of the poetic discourse at Saif al-Marri. Third: The results of the study (technical characteristics of his hair .